Есепте: 92 – (52 ⋅ 1 + 32 ⋅ 0) =

62 + 22 ⋅ 3 + 52 =

82 – (92 ⋅ 0 + 72) + 42 =

Артқа

Тексеру

lenaglukhova20 lenaglukhova20    1   23.11.2020 23:01    3

Ответы
bokshitskayan bokshitskayan  23.12.2020 23:04

1)40

2)180

3)52

Пошаговое объяснение:

92 – (52 ⋅ 1 + 32 ⋅ 0) =92—(52+0)=92—52=40

62 + 22 ⋅ 3 + 52 =62+66+52=128+52=180

82 – (92 ⋅ 0 + 72) + 42 =82—(0+72)+42=82—72=10+42=52

ПОКАЗАТЬ ОТВЕТЫ
dimentor13 dimentor13  23.12.2020 23:04

Пошаговое объяснение:

1.

1) 52*1 + 32*0 = 52

2) 92 - 52 = 40

2.

62 * 22*3 + 52 = 62 + 66 + 52 = 180

3.

1) 92 * 0 + 72 = 72

2) 82 - 72 + 42 = 52

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика